Clinical description of cardiovascular side effects in patients infected with COVID-19 virus (Revista Chilena de Rehabilitación y Actividad Física, 2022)
As of 2020, the damage caused by the COVID-19 infection in the patients’ systems begins to be described, ranging from mild, very serious and death. In this work, they compiled studies that incorporated clinical descriptions of the most frequent and deadly cardiovascular disorders (CA) triggered by the virus. Eighty indexed publications, published during 2020, were reviewed, in 33 of them we were able to obtain hard data from patients who presented CA triggered by COVID-19 with a history of underlying cardiovascular disease (CVD), among the most frequent were Thromboembolism (VTE ), myocarditis, acute coronary syndrome (ACS) and acute cardiac injury (ACL), these side effects of Covid-19 infection increased the severity of the patients and the risk of mortality, when they had CVD, the most frequent pathology It was hypertension and although diabetes mellitus is not a cardiovascular disease, it was the second, increasing vulnerability in COVID-19 patients, not because they are more prone to infection, but because they are highly represented in the world population , and their responses would be less favorable to the inflammatory effects of the virus.
Keywords: COVID-19; thromboembolism; myocarditis; acute coronary syndrome; acute cardiac injury; cardiovascular disease